Enhanced Shear Adhesion by Mechanical Interlocking of Dual‐Scaled Elastomeric Micropillars With Embedded Silica Particles. Issue 11 (14th August 2013) - Rahmawan, Yudi; Kang, Seong Min; Lee, Su Yeon; Suh, Kahp‐Yang; Yang, Shu; Izadi, Hadi; Penlidis, Alexander
Abstract Enhanced shear adhesion of mechanically interlocked dual‐scaled micropillars embedded with silica particles is demonstrated. Arrays of elastomeric polyurethane acrylate micropillars with variable pillar diameter, height, aspect ratio (AR = diameter/height), and spacing ratio (SR = pillar‐to‐pillar distance/diameter) are decorated with silica particles of 100 nm to 1 μm on the pillar heads. The high‐density protrusions provided by a silica particle assembly (1 μm diameter) on the micropillar heads (5 μm diameter, AR = 8, SR = 2) increase the shear adhesion strength by an order of magnitude from 4.1 (between pristine micropillars) to 48.5 N cm−2. The adhesion strength is proportional to the particle size and the AR of micropillars, and inversely proportional to the SR. A simple mathematical model is derived by incorporating the interdigitation state of interlocking adhesion forces generated by the contacts between pillars and particle protrusions. Our model and SEM images also suggest that only ≈20% of micropillars participate in the actual contact.<inline-graphic xlink:href="ark:/27927/pgg3wjd9c5p" content-type="mren201300149-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />